The fungal spore Annella capitata Srivastava from the Jurassic (Late Toarcian-Late Bajocian) Cañadón Asfalto Formation of Patagonia, Argentina - Olivera, Daniela Elizabeth (2014)
The fungal spore Annella capitata Srivastava is recorded for the first time in Argentina, within the continental Jurassic strata of the Cañadón Asfalto Formation, Cañadón Asfalto Basin, Patagonia. It is identified on pollen grains belonging to the Cheirolepideaceae, Araucariaceae and Podocarpaceae. This paper contrasts A. capitata with ubisch bodies (small sporopollenin spherules attached to the exine). A. capitata has the same characteristics in the different pollen taxa, while the ubish bodies exhibit taxon-dependent differences in ultrastructure, size and morphology. The presence of hyphae and spore germlings reinforces a fungal origin of A. capitata. The degree and type of deterioration associated with these fungal microfossils are presented. Based upon the ecological requirements of the plant families recognized in the Cañadón Asfalto palynoflora, it is inferred that A. capitata Srivastava thrived in low-energy environments under warm-temperate and humid conditions.